Harta Dan Kepemilikan (Batasan Saving Perspektif Ekonomi Islam) - Muflihul Fadhil; Febrian Permana; Amrul Muzan (Yayasan Marwah Madani Riau, 2024)
This research aims to provide an understanding of the nature of property and ownership as well as the limits of saving that every Muslim needs to understand in order to comply with the rules of the Al-Qur'an and hadith. Based on this understanding, it can be a guide for every believer in how to obtain, use and store the blessings of wealth that have been given by Allah SWT. This research method uses qualitative descriptives which briefly discuss the concept of wealth and the limits of saving or saving money from an Islamic perspective, based on literature studies from the Al-Qur'an and hadith. The research results show that; 1) The essence of wealth is a gift and favor from Allah which is used as a cause for the establishment of benefits for life; 2) The essence of ownership of property is that it completely belongs to Allah which He has given to humans with the aim of being able to use it as well as possible in accordance with Allah's provisions for the welfare of all mankind, and this property is a deposit that will be accounted for in the afterlife, starting from how to get it, use it and save it; 3) The limit of saving money from an Islamic perspective is to be precautionary (money demand for precautionary) not to hoard money, which means preventing carrying out obligations (Allah's rights). However, based on the current concept of modern financial management, saving is done using banking financial institutions, it can be ensured that savings money is managed in accordance with applicable regulations. This is where a customer is required to be able to choose sharia-based banking so that the results from managing savings are guaranteed to be halal in accordance with the concept of sharia